Alterations in the Relative Surface Velocity of Joint Following Anterior Cruciate Ligament Injury in a Sheep Model - Shekarforoush, Shekarforoush M.; Barton, Kristen; Atarod, Mohammad; Heard, Bryan J.; Sevick, John; Hart, David A.; Shrive, Nigel G. (CMBES Proceedings, 2016)
Osteoarthritis is characterized as a potentially disabling chronic disease, which can decrease the quality of life of individuals. To date, many aspects of osteoarthritis remain unclear but epidemiologic studies have shown that people with a history of joint injury (especially in the knee joint) are at a high risk of developing OA. Recently, it has been suggested that changes in a knee joint relative surface velocity correlate more consistently with cartilage damage after joint injury. The reason can be explained by the fact that the directions of surface shear forces are related to the direction of surface relative velocity. Thus, an objective of this study was to determine the relative surface velocity of the knee joint before and after ligament injury and to correlate the change in the relative velocity with cartilage damage in a sheep model. We derived analytical formulas to define the linear and angular velocity of the tibiofemoral component of a knee joint. The results are compatible with the motion of the joint during a normal gait cycle. The results also show that there were changes in the timing of the phases of the gait cycle between the intact and follow-up time points after injuries in the subjects, evidence of changes in the direction of the relative velocity. This study provides new information about the role of joint surface relative velocity of the knee joint after ligament injury, which can be considered as a potential mechanical factor for cartilage damage.